Household expenditure and accessibility of water in urban India. (October 2022) - Tirumala, Raghu Dharmapuri; Tiwari, Piyush
Accessibility and affordability are critical challenges for household water consumption in urban India. While the previous research on affordability and water tariff setting is substantial, the interplay of water access equity and its impact on household water expenditure is less understood due to the absence of granular household level data in India. This research draws upon the NSSO's 76th round of data collected across the country to explore the differences in water access and expenditure amongst various income categories. Using regression analysis, this paper investigates the association between the socio-economic, tenurial status, sources of water, sufficiency, and access related factors and the household expenditure on water. Results show that water is a scarce commodity for lower sections of society and that they are incurring higher costs, making the water relatively unaffordable. The research findings indicate that the policymakers and project proponents need to develop more targeted metrics for measuring the disparities and configure interventions that mitigate the inequalities in urban water provision.